Book review: ManiKumar K. A., Foreshadowing the Great Rebellion: The Vellore Revolt, 1806. (January 2023) - Bhattacharya, Niloshree
ManiKumar K. A., Foreshadowing the Great Rebellion: The Vellore Revolt, 1806. Hyderabad: Orient BlackSwan, 2021, 243pp., ₹695 (paperback). ISBN: 978354421181.